The Sulfinylsulfonation of alkynes for β‐Sulfinyl alkenylsulfone. Issue 14 (18th May 2022) - Zhang, Zhansong; Song, Qingmin; Feng, Chengjie; Wang, Zikun; Zhao, Wanjun; Ning, Yongquan; Wu, Yong
Abstract: Here we report the sulfinylsulfonation of alkynes to afford β‐sulfinyl alkenylsulfone products with a broad substrate scope, excellent functional group compatibility, and high yield. Moreover, the sulfinylsulfonation reaction of enyne can also be realized for constructing functionalized carbo‐ and heterocycles through a radical cascade cyclization process. Abstract : Sulfinylsulfonation of alkynes to afford β‐sulfinyl alkenylsulfone products with a broad substrate scope, excellent functional group compatibility, and high yield has been reported. Moreover, sulfinylsulfonation reaction of enyne can also be realized for constructing functionalized carbo‐ and heterocycles through a radical cascade cyclization process.